Effects of Consumption-Oriented versus Trophy-Oriented Fisheries on Muskellunge Population Size Structure in Northern Wisconsin. (1st November 2016) - Faust, Matthew D.; Hansen, Michael J.
Abstract: To determine whether a consumption-oriented fishery was compatible with a trophy-oriented fishery for Muskellunge Esox masquinongy, we modeled effects of a spearing fishery and recreational angling fishery on population size structure (i.e., numbers of fish ≥ 102, 114, and 127 cm) in northern Wisconsin. An individual-based simulation model was used to quantify the effect of harvest mortality at currently observed levels of recreational angling and tribal spearing fishery exploitation, along with simulated increases in exploitation, for three typical growth potentials (i.e., low, moderate, and high) of Muskellunge in northern Wisconsin across a variety of minimum length limits (i.e., 71, 102, 114, and 127 cm). Populations with moderate to high growth potential and minimum length limits ≥ 114 cm were predicted to have lower declines in numbers of trophy Muskellunge when subjected to angling-only and mixed fisheries at observed and increased levels of exploitation, which suggested that fisheries with disparate motivations may be able to coexist under certain conditions such as restrictive length limits and low levels of exploitation. However, for most Muskellunge populations in northern Wisconsin regulated by a 102-cm minimum length limit, both angling and spearing fisheries may reduce numbers of trophy Muskellunge as larger declines were predicted across all growth potentials. Our results may be useful if Muskellunge management options in northern Wisconsin are re-examined in the future. Received January 16, 2016; accepted July 4, 2016 Published online October 28, 2016